2005
DOI: 10.1182/blood-2004-08-3156
|View full text |Cite
|
Sign up to set email alerts
|

A subset of natural killer cells achieves self-tolerance without expressing inhibitory receptors specific for self-MHC molecules

Abstract: It is widely believed that self-tolerance of natural killer (NK) cells occurs because each NK cell expresses at least one inhibitory receptor specific for a host major histocompatibility complex (MHC) class I molecule. Here we report that some NK cells lack all known self-MHC-specific inhibitory receptors, yet are nevertheless self-tolerant. These NK cells exhibit a normal cell surface phenotype and some functional activity. However, they respond poorly to class I-deficient normal cells, tumor cells, or cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
575
2
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(608 citation statements)
references
References 65 publications
20
575
2
11
Order By: Relevance
“…Current models for NK cell education and tolerance regard the inhibitory input (or the lack of it) as important, either during the development to achieve functional maturity [39,40] To improve visualization, error bars (SEM) are only shown for the extreme curves. n 5 8 mice per group.…”
Section: Discussionmentioning
confidence: 99%
“…Current models for NK cell education and tolerance regard the inhibitory input (or the lack of it) as important, either during the development to achieve functional maturity [39,40] To improve visualization, error bars (SEM) are only shown for the extreme curves. n 5 8 mice per group.…”
Section: Discussionmentioning
confidence: 99%
“…However, such NK cells are self-tolerant because they are hyporesponsive after engagement of activating receptors. Conversely, NK cells that express inhibitory receptors for self-MHC are functionally competent [3,4]. Thus, in humans, it has been shown that KIR2DL2/L3 1 , KIR2DL1 1 or KIR3DL1 1 CD56 dim NK cells derived from donors expressing the corresponding HLA class I ligands (group C1 alleles, group C2 alleles and HLA allotypes with the Bw4 epitope, respectively) are more responsive to CD16 cross-linking and stimulation with class I negative target cells than other NK-cell subsets [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unclear whether the hyporesponsive phenotype is stable or whether it can be reversed in certain contexts. Indeed, during infection with Listeria monocytogenes, NK cells that lack inhibitory receptors for self-MHC can produce as much IFN-g as competent NK cells [4]. Interestingly, NK cells derived from b2-microglobulin-deficient mice, which are hyporesponsive after certain activating stimuli, are still able to control cytomegalovirus infection in vivo [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of one or more inhibitory Ly49 receptors is a key step by which the developing NK cells achieve full functional competency. 36,37 Our preliminary ex vivo analyses of fresh BM-derived NK cells revealed a significant reduction of Ly49A þ subset (44.0%) compared to WT. Similar reductions of Ly49A þ subset (41.1%) were seen in the spleenderived fresh NK cells (Figures 3a and b).…”
Section: Resultsmentioning
confidence: 93%